Macromolecular-clustered facial amphiphilic antimicrobials. Issue 1 (December 2018) - Rahman, Md; Bam, Marpe; Luat, Edgar; Jui, Moumita; Ganewatta, Mitra; Shokfai, Tinom; Nagarkatti, Mitzi; Decho, Alan; Tang, Chuanbing
Abstract Bacterial infections and antibiotic resistance, particularly by Gram-negative pathogens, have become a global healthcare crisis. We report the design of a class of cationic antimicrobial polymers that cluster local facial amphiphilicity from repeating units to enhance interactions with bacterial membranes without requiring a globally conformational arrangement associated with highly unfavorable entropic loss. This concept of macromolecular architectures is demonstrated with a series of multicyclic natural product-based cationic polymers. We have shown that cholic acid derivatives with three charged head groups are more potent and selective than lithocholic and deoxycholic counterparts, particularly against Gram-negative bacteria. This is ascribed to the formation of true facial amphiphilicity with hydrophilic ion groups oriented on one face and hydrophobic multicyclic hydrocarbon structures on the opposite face. Such local facial amphiphilicity is clustered via a flexible macromolecular backbone in a concerted way when in contact with bacterial membranes. Bacterial infections and antibiotic resistance are an increasing concern for the world. Here the authors report a class of cationic antimicrobial polymers that cluster local facial amphiphilicity from repeating units to enhance interactions with bacterial membranes without requiring a high unfavorable entropic loss.